1992
DOI: 10.1073/pnas.89.12.5690
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of the murine and human interleukin 9 receptor cDNAs.

Abstract: Interleukin 9 (IL-9) is a T-cell-derived lymphokine that induces the proliferation of various lymphold and hemopoietic cells. A cDNA done encoding the murine receptor was isolated by expression cloning in COS cells and screening with 12SI-labeled IL-9. Transient expression of this cDNA produced high-affinity binding sites for IL-9. The predcid 52-kDa protein contains a putative signal peptide and a pical trsembrane domain. A cDNA for the human homoogue was isolated by cross-hybridization. Transfection of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 28 publications
0
73
0
Order By: Relevance
“…Minor amounts of IL-9 may also be produced by Th2 and Th17 cells. IL-9 activates a heterodimeric receptor consisting of the cytokinespecific IL-9 receptor a chain (IL-9Ra) and the common c-chain [91]. Upon binding of IL-9 to its receptor, the kinases Jak1 and Jak3 are phosphorylated and subsequently activate Stat1, Stat3 and Stat5 [92][93][94].…”
Section: Il-9mentioning
confidence: 99%
“…Minor amounts of IL-9 may also be produced by Th2 and Th17 cells. IL-9 activates a heterodimeric receptor consisting of the cytokinespecific IL-9 receptor a chain (IL-9Ra) and the common c-chain [91]. Upon binding of IL-9 to its receptor, the kinases Jak1 and Jak3 are phosphorylated and subsequently activate Stat1, Stat3 and Stat5 [92][93][94].…”
Section: Il-9mentioning
confidence: 99%
“…It was recently shown that two of these latter residues are also important for activation of STAT1 (consensus sequence Tyr-Xaa-Pro-Gln) (Gerhartz et al, 1996). The box 3 motif is also found in the receptors for IL-7 (Goodwin et al, 1990), IL-9 (Renauld et al, 1992), IL-10 (Liu et al, 1994), and thrombopoietin (Vigon et al, 1992), in the OSMspecific receptor (OSMRP) (Mosley et al, 1996), and in the leptin receptor (OB-R) (Tartaglia et al, 1995). The OSMRP and the OB-R are related to gp130 in primary structure (23.3% and 20.7% overall amino acid identity, respectively) and in modular structure, featuring both Ig-like and FN III domains (Hibi et al, 1990;Tartaglia et al, 1995;Mosley et al, 1996).…”
Section: The Il-6 Signal Transduce< Gp130mentioning
confidence: 99%
“…Soluble IL7Rα (sIL7Rα) was identified in 1990 coincident with cloning of human cell-associated IL7Rα, and sIL7Rα is known to circulate in nanomolar concentrations (21)(22)(23)(24), but, to date, the biological function of sIL7Rα remains unclear. There are two primary mechanisms through which soluble cytokine receptors can be produced (17): shedding of membrane-bound receptors [e.g., TNF receptor 2 (25)] and alternative splicing leading to a protein lacking the transmembrane domain [e.g., IL-9Rα (26)]. Previous biochemical studies have demonstrated that sIL7Rα present in human plasma is primarily derived from alternative splicing and comprises an isoform lacking exon 6 (Δ6IL7Rα), as well as a unique 26-aa sequence as a result of a frame shift and a premature stop codon (24) (Fig.…”
mentioning
confidence: 99%